Remoção de metano dissolvido com câmara de dessorção em reator anaeróbio híbrido - Morandini, Naiara Ammes (2022)
In the anaerobic digestion process some by-products are formed, such as biogas. The presence of methane gas as a major constituent of biogas and the escape of this gas dissolved in the effluent of anaerobic reactors is a recurring problem, due to its potential for energy recovery and the fact that it is a contributor to the aggravation of the greenhouse effect. In this study, an Upflow Anaerobic Hybrid Reactor with a volume of 22.1 L and a Desorption Chamber (DC) with a volume of 15.7 L, was operated with support means corrugated rings of Polyvinyl chloride (PVC) used for the treatment of synthetic domestic wastewater. The main objective of the work was to evaluate the influence of the CD in the removal of methane gas dissolved in the effluent of the reactor, through the recirculation of the liquid in the unit, varying the ratios between air flow/affluent liquid (rQ) and the ratios between flow of the recirculation liquid/affluent liquid (rQL), in continuous flow and with renewal of the confined atmosphere from the waste gas. Tests were carried out based on the statistical planning elaborated with Central Composite Rotational Design (CCRD), in 153 days of monitoring. Dissolved methane removal efficiencies higher than 78% were obtained. The best control efficiencies of this gas, obtained by means of the desirability test, combined in certain dosages of air, whose best rQ ratios were 202 and the best rQL ratios were 1.95, presenting efficiencies of 98%. From the results, it was verified that the recirculation of the liquid in the DC contributed to higher removals of methane. The measured waste gas was around 0.5% methane. The volume of methane dissolved in the effluent of the anaerobic reactor represented 43% of the total average methane production in the reactor during the monitoring.